Combined Hamartoma of the Retina and Retinal Pigment Epithelium in a Patient with Gorlin Syndrome: Spontaneous Partial Resolution of Traction Caused by Epiretinal Membrane - José L. Sánchez-Vicente; Miguel Contreras-Díaz; Trinidad Rueda; Enrique Rodríguez de la Rúa-Franch; Fredy E. Molina-Socola; Cristina Vital-Berral; Asunción Alfaro-Juárez; Fernando López-Herrero; Ana Muñoz-Morales (Case Reports in Ophthalmological Medicine)
Purpose. To describe the case of spontaneous resolution of epiretinal membrane in a patient with Combined Hamartoma of the Retina and Retinal Pigment Epithelium (CHR-RPE), in the clinical context of Gorlin Syndrome (GS). Methods. Observational case report of a 12-year-old female patient is presented. The diagnosis of CHRRPE was made by OCT and fundus examination, which showed a mound of disorganized tissue originating from retina and retinal pigment epithelium. Epiretinal membrane (EM) was also detected. Genetic study was performed to confirm the diagnosis of GS. Results. The patient was observed for 39 months, showing spontaneous resolution of the traction caused by the EM and improvement in visual acuity (VA), which was 20/80 at initial presentation, rising to 20/40 after follow-up period. Conclusions. The presence of EM in CHR-REP is a cause of reduction of visual acuity. Management of this condition is controversial; however, we would like to highlight that spontaneous resolution of the traction caused by EM is possible, resulting in recovery of VA.